Anhydrous LiNbO3 Synthesis and Its Application for Surface Modification of Garnet Type Li-Ion Conductors. Issue 4 (1st April 2022) - Mann, Markus; Schwab, Christian; Ihrig, Martin; Finsterbusch, Martin; Martin, Manfred; Guillon, Olivier; Fattakhova-Rohlfing, Dina
Abstract : In our work we demonstrate a facile, water-free synthesis of amorphous lithium niobate (LiNbO3 ) layers. Our developed method also enables the coating of substrates in inert atmosphere with simple, industrial scalable methods. As verification, a 120 nm thin LiNbO3 layer was deposited on the garnet type lithium ion conductor Li6.45 Al0.05 La3 Zr1.6 Ta0.4 O12 (LLZTO) to improve its interface to lithium metal and reduce dendrite formation. The application of the thin film reduced the interface resistance between LLZTO and lithium metal to 1.02(13) Ω∙cm 2 and increased the critical current density for dendrite formation to at least 0.5 mA cm −2 . The chemical stability of the LiNbO3 thin film in contact with Li-metal was verified by SEM, XPS and ToF-SIMS.